Language lesson learned—foreign-origin teachers and their effect on students' language skills - Lisa Sofie Höckel (Journal of Population Economics, 2024)
International migration increases classroom diversity around the world, but little is known about the effect of foreign-origin teachers on students' academic achievement. This study investigates whether foreign-origin teachers causally affect their students' academic performance. Exploiting within-student variation in assignment to teachers in Germany, I find that teachers who are immigrants or descendants of immigrants significantly increase the reading comprehension of their students in secondary school, but do not affect their math skills. This study is the first to investigate bilingualism as a potential mechanism and shows that the effect on reading comprehension is driven by bilingual foreign-origin teachers. Given their own experience in language learning, they seem exceptionally well-equipped to teach languages. This study contributes to the scant evidence on the causal relationship between teachers' foreign origin and students' academic achievement in light of a large and persistent achievement gap between native and foreign-origin students.
Keywords: 330; Bilingualism; Education; Language skills; Migration; Role model effect; Teacher bias